2021
DOI: 10.1007/s10517-021-05324-y
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Enhances the Anti-Metastasis Effect of Oxaliplatinliplatin on Colorectal Cancer Liver Metastasis

Abstract: The anti-metastasis effect of oridonin in combination with oxaliplatin on colorectal cancer liver metastasis was studied using a BALB/c nude mouse model. The liver condition, bloody ascites, cholestasis, and liver metastasis scores in the three groups receiving oxaliplatin combined with oridonin were significantly milder than in the control group and importantly the anti-migratory effect of oxaliplatin combined with oridonin was obviously the strongest (p<0.05). Oridonin possessed no hepatotoxicity; instead, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In recent years, numerous studies have demonstrated that oridonin has a vital role in anti-inflammatory [6], anti-cancer [7,8], antibacterial [9], anti-sepsis [10], neuroprotection [11], immune regulation and other pharmacological and physiological aspects [12]. Among them, its anticancer activity has been widely reported in nasopharyngeal cancer [13], esophageal cancer [14], gastric cancer [15], colorectal cancer [16,17], pancreatic cancer [18], gallbladder cancer [19], breast cancer [20], ovarian cancer and other malignant cancers [21,22]. And the anticancer mechanism of oridonin is involved with inhibition of proliferation, induction of apoptosis, autophagy and inhibition of migration and invasion [23].…”
Section: Ivyspringmentioning
confidence: 99%
“…In recent years, numerous studies have demonstrated that oridonin has a vital role in anti-inflammatory [6], anti-cancer [7,8], antibacterial [9], anti-sepsis [10], neuroprotection [11], immune regulation and other pharmacological and physiological aspects [12]. Among them, its anticancer activity has been widely reported in nasopharyngeal cancer [13], esophageal cancer [14], gastric cancer [15], colorectal cancer [16,17], pancreatic cancer [18], gallbladder cancer [19], breast cancer [20], ovarian cancer and other malignant cancers [21,22]. And the anticancer mechanism of oridonin is involved with inhibition of proliferation, induction of apoptosis, autophagy and inhibition of migration and invasion [23].…”
Section: Ivyspringmentioning
confidence: 99%
“…Oridonin, a natural terpenoids found in traditional Chinese herbal medicine, impedes inflammasome assembly by forming covalent bond with NLRP3 Cys279 (72). Oridonin administration effectively prevents the formation of colorectal cancer liver metastasis (73) and improves oxaliplatin efficacy (74). Oridonin derivative, with potent anticancer effects, has been very recently synthesized (75).…”
Section: Inflammasome Targeting Drugs: Potential Anti-cancer Therapeuticmentioning
confidence: 99%
“…Oridonin has previously been investigated for its therapeutic effects on the following types of caners: colon, 2 , 3 , 6 , 10 , 11 breast, 12 , 13 pancreatic, 14 , 15 lung, 16 , 17 , 18 gallbladder, 19 prostate, 20 ovarian, 21 oesophageal, 22 oral, 23 , 24 bladder, 25 liver 26 and other cancers. It has been reported that the inhibitory effect of oridonin on proliferation of gastric cancer is mainly related to inducing apoptosis and promoting autophagy, 27 , 28 , 29 without further in‐depth discussions.…”
Section: Introductionmentioning
confidence: 99%